Job Satisfaction of Vocational High School Student Graduates - Nina Kartina; Ana Ana; Cica Yulia (Publikasi Indonesia, 2023)
This type of research is descriptive qualitative with the aim of knowing the job satisfaction of graduates of vocational high schools in the fashion skills program. purwakarta. Data were obtained through interviews, field notes and data were analyzed using a frequency distribution. Based on the results of data analysis, it can be concluded that alumni of the tabus vocational high school students in the category of environmental factors are satisfied with their work environment. For the category of work environment, they are quite satisfied, which means that the comfort of the existing workplace has made them comfortable. For the alumni salary category, the students of the Vocational School of the Fashion Design expertise program were very satisfied because according to them the salary given was in accordance with the UMR. Based on the category of interaction among co-workers, alumni of the Vocational School of the Fashion Design expertise program said they were satisfied and quite satisfied with the same number, meaning that alumni of the Vocational High School students of the Fashion Design expertise program did not feel there was a problem with their co-workers. Finally, in the category of interaction with superiors, alumni of the Vocational School of Fashion Design expertise program were quite satisfied, which means that communication between superiors and subordinates was well established.